Modelling Inflation Dynamics in Transition Economies: The Case of Ukraine - Boriss Siliverstovs; Olena Bilan (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
The paper explores dynamics of inflation in Ukraine in the period of relative macroeconomic stability. The analysis of interrelationship between inflation, money growth, wage growth, and a proxy for devaluation expectations is based on impulse responses and variance decomposition of a vector autoregression model. We find that changes in devaluation expectations appear to be the most important factor driving price development, while money supply growth has negligible impact on inflation. In addition, our results evidence of high degree of inflation inertia in the economy, which may reflect the specific institutional settings of Ukrainian economy.
Keywords: C32; E31; P24; 330; Transition economy; Inflation